2021
DOI: 10.1371/journal.pone.0258542
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent girls and young women’s PrEP-user journey during an implementation science study in South Africa and Kenya

Abstract: Successful scale-up of PrEP for HIV prevention in African adolescent girls and young women (AGYW) requires integration of PrEP into young women’s everyday lives. We conducted interviews and focus group discussions with 137 AGYW PrEP users aged 16–25 from South Africa and Kenya. Individual and relational enablers and disablers were explored at key moments during their PrEP-user journey from awareness, initiation and early use through persistence, including PrEP pauses, restarts, and discontinuation. PrEP uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
84
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 46 publications
14
84
0
Order By: Relevance
“…Second, they call for greater engagement with AGYW in demand-creation. In agreement with observations amongst AGYW in Kenya and South Africa [ 26 ], they point towards the need to identify peers who can come forward and share their experiences of being on PrEP, and serve as role models or PrEP ambassadors. The healthcare providers also noted that they could play a more active role in identifying and recruiting AGYW to PrEP.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Second, they call for greater engagement with AGYW in demand-creation. In agreement with observations amongst AGYW in Kenya and South Africa [ 26 ], they point towards the need to identify peers who can come forward and share their experiences of being on PrEP, and serve as role models or PrEP ambassadors. The healthcare providers also noted that they could play a more active role in identifying and recruiting AGYW to PrEP.…”
Section: Discussionsupporting
confidence: 76%
“…They also called for a disassociation of PrEP from HIV treatment. These recommendations resonate with findings from a recent qualitative study with AGYW in South Africa and Kenya, which found adolescent-friendly and integrated sexual and reproductive health services to facilitate PrEP uptake [ 26 ]. In fact, a review of early lessons from PrEP demonstration projects in SSA found PrEP initiation and impact amongst AGYW to be greater in projects that integrated PrEP into youth-friendly clinics that combined a range of different sexual and reproductive health services [ 10 ].…”
Section: Discussionsupporting
confidence: 71%
“…Whereas the current literature on integrated PrEP-FP delivery often refers to “FP clinics” as a uniform delivery setting, our study revealed key points of heterogeneity between two FP clinics that influenced implementation (e.g., organizational mission, clinic flow). Our finding that the youth-friendly clinic was potentially “low-hanging fruit” for this HIV prevention innovation is consistent with other projects and programs in Kenya [ 6 ], South Africa [ 33 , 34 ], and Malawi [ 35 ], which similarly reported that providers at these venues were generally open to delivering PrEP and that AGYW like obtaining services in these settings. The implications of our findings for scale-up are even clearer when placed within the context of a typology of health facilities recently developed by Dunbar et al based on their assessment of 20 facilities in Kenya and Zimbabwe [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…Studies in this first domain have measured PrEP use (e.g., uptake, adherence, continuation) and its predictors [ 5 – 7 ] and engaged AGYW to understand their PrEP decision-making [ 6 , 8 – 10 ]. Qualitative investigations have identified a variety of barriers to AGYW PrEP use, such as low HIV risk perception [ 11 – 13 ]; high stigma for being sexually active [ 14 ]; lack of financial independence [ 15 ]; and low social support for PrEP use [ 13 , 16 – 18 ]. These findings have motivated the second major area of research, centered on developing and testing delivery models and interventions to support AGYW in PrEP use.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, mobile health clinics operating in locations frequented by AGYW are feasible, acceptable and improve PrEP uptake [ 25 ]. PrEP integration into sexual reproductive health services also facilitates uptake among AGYW [ 26 ]. These interventions could improve PrEP uptake among AGYW elsewhere in SSA.…”
Section: Discussionmentioning
confidence: 99%